First gen : a memoir - Campoverdi, Alejandra (Grand Central Publishing, Hachette Book Group, 2023)
"From former White House aide to President Obama and Harvard graduate, Alejandra Campoverdi, comes a riveting and unflinching memoir on navigating social mobility as a first gen Latina, offering a broad examination of the unacknowledged emotional tolls of being a trailblazer. To be a First and Only in America is a delicate balancing act of surviving where you come from while acting like you belong where you're going. Alejandra Campoverdi has been a child on welfare, a White House aide to President Obama, a gang member's girlfriend, and a candidate for U.S. Congress. She's ridden on Air Force One and in G-rides. She's modeled on the pages of Maxim and had a double mastectomy. Living a life of contradictory extremes often comes with the territory when you're a 'First and Only.' It also comes at a price. With candor and heart, Alejandra retraces her trajectory as a Mexican American woman raised by an immigrant single mother in Los Angeles, foregoing the tidy bullet points of her resume and shining a light on the spaces between them instead. What emerges is a moving testimony of personal struggle and triumph that shatters the one-dimensional glossy narrative we are often sold of what it takes to achieve the American Dream. Alejandra uses her own experiences to illustrate the emotional tolls First and Onlys often face that are widespread yet rarely acknowledged, providing a road to truth and healing in the process. It is a timely and revealing reflection, as social class continues to be a key determinant of career success. Part memoir, part manifesto, First Gen is a story of generational inheritance, aspiration, and belonging--a poignant journey to 'reclaim the parts of ourselves we sacrificed in order to survive.'"--